A study in Mental Analysis- prophethood necessity - اياد نعيم مجيد ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
In our study, we dealt with the subject of prophethood, and its necessity was proved by the rational proofs of the philosophers of the various philosophical schools (Peripatetic, Orientalist, and Transcendental). And we have proven by definitive evidence that the existence of the prophets is a life necessity to achieve the divine purpose of creation, otherwise the purpose will be abrogated, the purpose is abrogated, and the purpose is nullified by an ugly act, and the ugly does not come from the transcendent sage. The prophets, despite their different ranks and positions, are still few, and they are the best among people from all sides. By means of revelation, they are in the highest degrees of perfection in relation to true sciences and matters related to religious rulings and political matters. In their different ranks and positions, the ranks of revelation differ, so the Prophet Muhammad (may Allah prayers and peace be upon him and his family and peace be upon him) was at the top of the ranks of revelation, because he reached what other prophets could not reach, to honor the holy and divine place